Marine climate change and global fisheries:: the silence of Social Sciences - Martins, Andreza; Guivant, Julia Silvia (Sustainability in Debate, 2017)
The current challenges posed by global warming have brought the oceans to the centre of political and academic debates. Technical/scientific reports claim excessive CO2 emissions have reduced the thermoregulatory capacity of oceans. Substantial changes in basic chemical conditions associated with acidification have broad implications for marine life and lead to socio-economic consequences, particularly affecting food security. There are numerous knowledge gaps about the complex relations between marine climate change and human populations. This paper contributes to fill these gaps by analysing the literature produced in the Social Sciences field. Main findings highlight the nearly total absence of social disciplines, with the exception of economics. Research gaps are significant in view of the urgency and seriousness of the growing natural and social processes that are underway in the daily life of contemporary societies.